Predicting Addiction Tendency in Adolescents Based on Dark Personality Traits, Social Isolation, and Psychological Hardiness - Shafiei, Mohammad; Pishbin, Mohammad Sadegh; Akbari, Sara; Sharifi, Fatemeh (KMAN Counseling & Psychology Nexus, 2025)
The present study aimed to predict the tendency toward addiction in adolescents based on dark personality traits, social isolation, and psychological hardiness. This study is applied in its objective, quantitative in nature, and employs a descriptive-correlational statistical approach. The study population included all adolescents enrolled in upper secondary schools in Shiraz during the year 2025. The sample consisted of 200 adolescents selected through cluster sampling from secondary schools in District 2 of Shiraz. In the field phase, quantitative data on the variables were collected using the following instruments: the Addiction Tendency Questionnaire by Mousavi et al. (2008), the Dark Triad Personality Questionnaire by Johnson and Webster (2010), the Social Isolation Questionnaire by Chalabi and Amirkafi (2004), and the Psychological Hardiness Questionnaire by Kobasa (1982). The data collected from the questionnaires were analyzed using SPSS version 28. To examine the research hypotheses, Pearson correlation tests and multiple regression analysis were used. The results showed that the dimensions of dark personality traits, psychological hardiness, and social isolation collectively accounted for 36% of the variance in addiction tendency scores. Furthermore, the Machiavellianism component positively and significantly predicted addiction tendency (β = 0.298, p = .001). The antisocial component also positively and significantly predicted addiction tendency (β = -0.328, p = .001). The cognitive component of psychological hardiness negatively and significantly predicted addiction tendency (β = -0.267, p = .005). Additionally, social isolation positively and significantly predicted addiction tendency (β = 0.429, p = .001). Therefore, addiction tendency can be predicted by dark personality traits, social isolation and psychological hardiness.